A NEW GENUS AND SPECIES OF GRACILLARIIDAE (LEPIDOPTERA) FEEDING ON FLOWERS OF ACACIA MACRACANTHA WILLD. (MIMOSACEAE) IN CHILE (Acta Entomológica Chilena, 2022)
The adult, larvae, and pupae of a new genus and species of Gracillariidae, Chileoptilia yaroella Vargas & Landry are described and illustrated from Chile (Arica Province). The larvae feed on flowers of Acacia macracantha Willd. (Mimosaceae) and their chaetotaxy is more complete than for other Gracillariidae.